Chapter 4 Male Supremacism and Ideological Masculinity - Roose, Joshua M. (Taylor & Francis, 2020)
Focused on the emergence of US President Donald Trump, the United Kingdom's departure from the European Union, and the recruitment of Islamic State foreign fighters from Western Muslim communities, this book explores the ways in which the decay and corruption of key social institutions has created a vacuum of intellectual and moral guidance for working people and deprived them of hope and an upward social mobility long considered central to the social contract of Western liberal democracy. Examining the exploitation of this vacuum of leadership and opportunity by new demagogues, the author considers two important yet overlooked dimensions of this new populism: the mobilization of both religion and masculinity. By understanding religion as a dynamic social force that can be mobilized for purposes of social solidarity and by appreciating the sociological arguments that hyper-masculinity is caused by social injury, Roose considers how these key social factors have been particularly important in contributing to the emergence of the new demagogues and their followers. Roose identifies the challenges that this poses for Western liberal democracy and argues that states must look beyond identity politics and exclusively rights-based claims and, instead, consider classical conceptions of citizenship.